An integrated model of financial technology adoption and environmental performance: The role of green innovation - Adelia Dwi Nurisaputri (Universitas Ahmad Dahlan, 2025)
Purpose-This study examines the effect of fintech adoption on environmental performance and analyzes the mediating role of green innovation among Batik MSMEs in Yogyakarta, Indonesia. The study aims to determine whether the use of digital financial tools encourages environmentally oriented innovation and whether such innovation contributes to improved environmental outcomes. Methodology-A quantitative approach was employed by surveying 124 Batik MSMEs selected through purposive sampling. Data were analyzed using PLS-SEM to evaluate the direct effects of fintech adoption and the mediating mechanism of green innovation. All constructs were measured using validated indicators adapted from previous studies. Findings-The results show that fintech adoption exerts a positive and significant effect on green innovation. However, its influence on environmental performance is positive but insignificant. Green innovation demonstrated a negative and non-significant influence on environmental performance, suggesting that existing innovation efforts have not been able to generate observable environmental gains. As a result, green innovation fails to serve as a mediating mechanism between fintech adoption and environmental performance. Research Limitations-The study is limited to Batik MSMEs in Yogyakarta, Indonesia, and uses purposive sampling with self-reported data, which may reduce generalizability. Conceptually, the model includes only fintech adoption, green innovation, and environmental performance, excluding other relevant factors that may influence sustainability outcomes. Novelty-This study contributes to the literature by integrating fintech adoption and green innovation within an environmental performance framework specific to traditional creative industries. The findings highlight that fintech adoption may encourage innovation, but such innovation alone is insufficient to improve environmental outcomes, underscoring the need for stronger environmental capabilities and policy support for sustainability in MSMEs.